Expression of the gene for inducible nitric oxide synthase in experimental glomerulonephritis in the rat. - Cook, H T (1994)
Nitrite, a stable product of nitric oxide (NO), is synthesized in vitro by glomeruli in experimental glomerulonephritis. We have now studied the expression of the gene for inducible NO synthase (iNOS) in accelerated nephrotoxic nephritis (NTN). The purpose of the study was to confirm in vivo induction of iNOS in this model of immune complex disease, and to relate the onset of induction and the level of expression to pathogenic events in the model. Glomeruli from rats with NTN were isolated at 6 h, 24 h and 2, 4 and 7 days and total RNA extracted. RNA (10 micrograms) was reverse transcribed and polymerase chain reaction (PCR) was performed with primers homologous to rat vascular smooth muscle iNOS and rat beta actin. A 222-base PCR product corresponding to iNOS mRNA was present in all experimental animals. iNOS expression was also found in activated macrophages, neutrophils and IL-1-stimulated but not unstimulated mesangial cells. Quantitative competitive PCR was carried out on glomerular samples using a 514-bp mutant of a 735-bp PCR product. iNOS expression was present at low levels in normal glomeruli and was markedly enhanced at 6 h after the induction of glomerulonephritis and peaked at 24 h. Increased iNOS expression persisted to day 7. beta actin mRNA levels were similar in all glomerular specimens. This study demonstrates that there is in vivo induction of iNOS in immune complex glomerulonephritis, corresponding to the generation of nitrite we have previously reported. iNOS gene expression is detectable within 6 h of induction of NTN, indicating the onset of gene transcription is closely related to the initial formation of immune complexes.